2009
DOI: 10.1016/j.visres.2009.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring gaze when categorizing faces’ sex: Evidence from eye-tracking data

Abstract: Previous research has shown that during recognition of frontal views of faces, the preferred landing positions of eye fixations are either on the nose or the eye region. Can these findings generalize to other facial views and a simpler perceptual task? An eye-tracking experiment investigated categorization of the sex of faces seen in four views. The results revealed a strategy, preferred in all views, which consisted of focusing gaze within an 'infraorbital region' of the face. This region was fixated more in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
66
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 70 publications
14
66
1
Order By: Relevance
“…The deliberate condition, on the other hand, conforms to the instructed viewing strategy, landing on both the eyes and the mouth region and generally more spread out across the stimulus-space. This pattern constitutes the average pattern of face perception, reliably found for young Caucasian individuals viewing static face stimuli in eye-tracking studies (e.g., Sæther et al, 2009). Furthermore, several face perception studies, which did not directly instruct differential viewing modes, nevertheless found separable viewing patterns interpreted to be differential viewing strategies (cp.…”
Section: Discussionsupporting
confidence: 53%
“…The deliberate condition, on the other hand, conforms to the instructed viewing strategy, landing on both the eyes and the mouth region and generally more spread out across the stimulus-space. This pattern constitutes the average pattern of face perception, reliably found for young Caucasian individuals viewing static face stimuli in eye-tracking studies (e.g., Sæther et al, 2009). Furthermore, several face perception studies, which did not directly instruct differential viewing modes, nevertheless found separable viewing patterns interpreted to be differential viewing strategies (cp.…”
Section: Discussionsupporting
confidence: 53%
“…We have provided experimental evidence that our participants complied with this intention (this in itself is an important result). What is crucial is that this exogenous cueing then affected face recognition accuracy, highlighting the importance of the location of the first fixation for accurate face encoding, processing, and recognition (see e.g., Hsiao & Cottrell, 2008) and the re-orienting of fixations to the preferred landing position (Saether, Van Belle, Laeng, Brennen, & Øvervoll, 2009). Most importantly, the location of the first fixation did indeed predict recognition accuracy, whereby Black faces were better recognised when the first fixation was to the nose than when the first fixation was to the eyes and the converse was true for White faces.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that women spend more time looking at the eyes whereas men pay more attention to central parts of faces (nose, mouth), indicating a more globally oriented processing [30] based on a centred viewpoint compared to more fixations at the eyes in a local strategy [28]. Moreover, men exhibit greater interest in opposite-sex faces than women [31] and value attractiveness higher than women [32], [33] which is reflected in stronger recruitment of reward-related areas in men viewing attractive female faces [34].…”
Section: Discussionmentioning
confidence: 99%